Aminosäuren als „leaf movement factors”: Pflanzenabwehrstoffe X : Über die biologische Chemie der Mimosaceen II - Schildknecht, Hermann; Tauscher, Bernhard; Pesh-Imam, Munir; Beltle, Wolfgang; Kunzelmann, Peter; Schneider, Dieter (The Science of nature, 1978)
The cause of endogenous chemonasty is discussed. Mimosa pudica extract contains several substances which were recognized as active and called leaf movement factors. Among these active principles are amino acids and mixtures of amino acids.